2009
DOI: 10.1177/1010539509351184
|View full text |Cite
|
Sign up to set email alerts
|

Income-Related Health Inequalities in Korea

Abstract: Data from the 2001 Korean National Health and Nutrition Examination Survey and the ill health concentration index (CI) were used to examine income-related health inequalities among Koreans. Participants (>19 years old) were requested to provide information regarding monthly household income, expenditures, subjective living conditions, and health status. Ill health was determined both subjectively through self-rated health (SRH) scores and objectively through the number of diseases (ND). At the individual le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…Studies have shown that socioeconomically disadvantaged groups have disproportionately higher levels of ill health and increased risks of depression. There are concerns that the increasing economic inequalities in South Korea may contribute to higher levels of depression among low income groups [ 11 , 23 ]. Low material standards have also been associated with an increased risk of depression [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that socioeconomically disadvantaged groups have disproportionately higher levels of ill health and increased risks of depression. There are concerns that the increasing economic inequalities in South Korea may contribute to higher levels of depression among low income groups [ 11 , 23 ]. Low material standards have also been associated with an increased risk of depression [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the economic status of an individual, studies have shown that a family’s transfer of money often continues throughout the life course of a child and leads to the reproduction of income inequality because there are positive associations between parents’ income and the prospect of intergenerational material transfer [ 9 ]. Such findings are significant because income inequality has risen noticeably since the 1997 economic crisis in South Korea, with income related health inequality escalating as low SES groups show a disproportionate level of ill health [ 10 , 11 ]. Hence, it is essential to understand how current and childhood economic status affect the depression levels of individuals because financial deprivation has been known to be associated with higher risks of depression throughout the life course of an individual.…”
Section: Introductionmentioning
confidence: 99%
“…12 Even in Japan and South Korea, where the population enjoys one of the longest and healthiest life expectancy from birth, a social gradient in various health outcomes exists: all-cause mortality increases with decreasing levels of education 13 ; mortality rates from injury and accidents is higher among lower occupational grade males, 14 functional decline increases with decreasing income, 15 as does self-rated health and number of chronic diseases. 16 In addition to a socioeconomic gradient, health inequities exist across the region by gender, Indigenous peoples (Table 1), 17 and minority ethnic groups. In China and India, for example, under-5 mortality rates are higher in girls than in boys; however, progress has been made toward narrowing the gender gap in countries such as Bangladesh.…”
Section: Inequities In Health Within Countriesmentioning
confidence: 99%
“…During this period, some scholars have transferred the concepts of income inequality and opportunity inequality to health inequality and have made preliminary interpretations of their connotations [13][14][15][16]. Scholars in different countries have also tried to measure health inequalities using single indicators such as mortality, life expectancy and self-rated health index and found that there are significant health inequalities in different countries such as New Zealand, South Korea and Chile [17][18][19][20]. With the complexity of health connotation, some scholars have begun to use input-output indicators to evaluate the allocation efficiency of medical and health resources at the hospital or regional level [21][22][23], with a view to providing empirical support for a more scientific grasp of regional public health levels.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%